Cultivating Work Readiness Through Psychological Capital and Social Support: A Transformational Learning Perspective - Syalwa Marliza; Cut Metia (Al-Qalam Institute, 2026)
The transition from higher education to employment remains difficult in Indonesia, where persistent educated unemployment signals that academic credentials alone no longer guarantee work readiness, and where the psychological and social resources that shape this readiness are still examined separately rather than together. This study aims to analyze the influence of psychological capital and social support on the work readiness of final-year students in Medan, both partially and simultaneously. Employing a quantitative explanatory design, data were collected through a cross-sectional survey of 120 students selected by purposive sampling and analyzed using multiple linear regression with IBM SPSS Statistics. The results show that psychological capital and social support simultaneously exert a positive and significant effect on work readiness (F = 529.857; p < 0.001), with psychological capital the dominant predictor (β = 0.750) compared to social support (β = 0.231). The implication is that transformational education and learning should deliberately cultivate students' internal psychological resources, positioning resilience and self-efficacy as engineered outcomes of institutional strategy rather than incidental byproducts.